Mechanical Properties and Performance Evaluation of Polypropylene (PP)/Lalang Grass Composite - a/l Asokan, Arravinthan (IRC, 2016)
Due to climate change problem, there is a growing interest in using natural fiber as a green and environmental friendly alternative compared to artificial fiber. One of natural fibers that has been studied is lalang grass fiber, which grows abundantly and wildly in tropical countries including Malaysia. Although several studies were reported, these studies were vague especially when focusing on the effects of alkali treatment and compatibilizer on mechanical properties of the composites. Therefore, the objective of this study was to evaluate the effects of sodium hydroxide (NaOH) and/or compatibilizing agent (MAPP) on the mechanical properties of PP/lalang composite. To perform this evaluation, four different blends of PP/lalang grass composites under the 70/30 wt% composition were prepared. Each blend was either exposed to alkali treatment, mixed with compatibilizer or both.